INCOME. - Sweeney, Henry W. (The Accounting Review, 1933)
Income is the economic benefit coming in during a period of time. It consists of current income and of capital gains and losses. The general accounting habit of regarding income as though it were synonymous with realized income, although of some usefulness in practical affairs because it tends to substitute fact for fancy, should be more dearly recognized as both illogical and generally causative of the compilation of false information. All the income–realized, unrealized, and the total thereof–coming into existence during a period should be credited to that period, but the realized should continue to be separated from the unrealized.